Overview of Extensively Employed Polymeric Carriers in Solid Dispersion Technology - Nair, Athira R.; Lakshman, Yarlagadda Dani; Anand, Vullendula Sai Krishna; Sree, K. S. Navya; Bhat, Krishnamurthy; Dengale, Swapnil J. (AAPS PharmSciTech, 2020)
Solid dispersion is the preferred technology to prepare efficacious forms of BCS class-II/IV APIs. To prepare solid dispersions, there exist a wide variety of polymeric carriers with interesting physicochemical and thermochemical characteristics available at the disposal of a formulation scientist. Since the advent of the solid dispersion technology in the early 1960s, there have been more than 5000 scientific papers published in the subject area. This review discusses the polymeric carrier properties of most extensively used polymers PVP, Copovidone, PEG, HPMC, HPMCAS, and Soluplus® in the solid dispersion technology. The literature trends about preparation techniques, dissolution, and stability improvement are analyzed from the Scopus® database to enable a formulator to make an informed choice of polymeric carrier. The stability and extent of dissolution improvement are largely dependent upon the type of polymeric carrier employed to formulate solid dispersions. With the increasing acceptance of transfer dissolution setup in the research community, it is required to evaluate the crystallization/precipitation inhibition potential of polymers under dynamic pH shift conditions. Further, there is a need to develop a regulatory framework which provides definition and complete classification along with necessarily recommended studies to characterize and evaluate solid dispersions.